Understanding Obesity and the Role of Pharmacological Treatments: Insights for Health and Fitness Enthusiasts - Agnieszka Starzyk; Piotr Charzewski (Quality in Sport)
Obesity results from disruptions in the regulation of body weight, driven by complex interactions between genetic and environmental factors. Genetic forms, such as monogenic and syndromic obesity, are rare but severe conditions often presenting with early-onset obesity, eating disorders, and a range of comorbidities. These forms of obesity pose significant challenges to treatment and health management. While historically managed through lifestyle interventions, recent advances in targeted therapies, including GLP-1 receptor agonists, MC4R agonists, and other pharmacological options, have shown significant potential in addressing genetic and syndromic obesity. These treatments, when combined with lifestyle modifications and surgical interventions, represent a step forward in improving health outcomes and quality of life for affected individuals. The integration of genetic diagnostics into clinical practice is critical to identifying appropriate candidates for these therapies and personalizing treatment plans to address the heterogeneous nature of obesity. Continued research into the molecular mechanisms and biomarkers of obesity is essential for refining these strategies, ensuring equitable access, and ultimately reducing the global health burden of obesity.